![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(4x-\sqrt{x^2-4x+4}=4x-\sqrt{\left(x-2\right)^2}=4x-\left(x-2\right)=3x+2\)
b) \(3x+\sqrt{9+6x+x^2}=3x+\sqrt{\left(x+3\right)^2}=3x-\left(x+3\right)=2x-3\)
c) \(\frac{x+6\sqrt{x}+9}{x-9}=\frac{\left(\sqrt{x}+3\right)^2}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}=\frac{\sqrt{x}+3}{\sqrt{x}-3}\)
d) \(\frac{\sqrt{x^2+4x+4}}{x+2}=\frac{\sqrt{\left(x+2\right)^2}}{x+2}=\frac{\left|x+2\right|}{x+2}\)( 1 )
với x < -2 thì : \(\left(1\right)\Leftrightarrow\frac{-\left(x+2\right)}{x+2}=-1\)
với x > -2 thì : \(\left(1\right)\Leftrightarrow\frac{\left(x+2\right)}{x+2}=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Với x<-3 ta có:
\(x+3+2\sqrt{x^2-9}=\sqrt{-\left(x+3\right)}.\sqrt{-\left(x+3\right)}+2\sqrt{-\left(x+3\right)}.\sqrt{3-x}\)
\(=\sqrt{-\left(x+3\right)}.\left(\sqrt{-\left(x+3\right)}+2\sqrt{3-x}\right)\)
\(6-2x+\sqrt{x^2-9}=\sqrt{3-x}\left(2\sqrt{3-x}+\sqrt{-\left(x+3\right)}\right)\)
Từ đó suy ra \(M=\frac{\sqrt{-\left(x+3\right)}}{\sqrt{3-x}}hayM=\sqrt{\frac{\left(x+3\right)}{\left(x-3\right)}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{x+3+2\sqrt{x^2-9}}{2x-6+\sqrt{x^2-9}}=\frac{\left(\sqrt{x+3}\right)^2+2\sqrt{x+3}\sqrt{x-3}}{2.\left(\sqrt{x-3}\right)^2+\sqrt{x+3}\sqrt{x-3}}\)
\(=\frac{\sqrt{x+3}\left(\sqrt{x+3}+2\sqrt{x-3}\right)}{\sqrt{x-3}\left(2\sqrt{x-3}+\sqrt{x+3}\right)}=\frac{\sqrt{x+3}}{\sqrt{x-3}}\)
\(=\frac{\sqrt{x^2-9}}{x-3}\)
C = \(=\frac{x+3+2\text{ }\sqrt{\left(x-3\right)\left(x+3\right)}}{2\left(x-3\right)+\sqrt{\left(x+3\right)\left(x-3\right)}}=\frac{\sqrt{x+3}\left(\sqrt{x+3}+2\sqrt{x-3}\right)}{\sqrt{x-3}\left(2\sqrt{x-3}+\sqrt{x+3}\right)}=\frac{\sqrt{x+3}}{\sqrt{x-3}}\)